Temporary overpessimism: Job loss expectations following a large negative employment shock - Julian Emmler; Bernd Fitzenberger (Economics of Transition and Institutional Change, 2021)
Job loss expectations were widespread amongst workers in East Germany following reunification with West Germany. Though experiencing a large negative employment shock, East German workers were nevertheless overpessimistic immediately after reunification with respect to their job loss risk. Over time, job loss expectations fell and converged to West German levels, which was driven by a stabilizing economic environment and by an adaptation of the interpretation of economic signals with workers learning to distinguish individual risk from firm-level risk. In fact, conditional on actual job loss risk, East German workers quickly caught up to West Germans regarding the share of correctly predicted job losses.
Keywords: 330; expectations; job loss; transition economies